Infectivity of nanovirus DNAs: induction of disease by cloned genome components of Faba bean necrotic yellows virus - Timchenko, T.; Katul, L.; Aronson, M.; Vega-Arreguín, J. C.; Ramirez, B. C.; Vetten, H. J.; Gronenborn, B. (Journal of General Virology, 2006)
Circumstantial evidence suggests that the genome of Faba bean necrotic yellows virus (FBNYV), a nanovirus, consists of eight distinct, circular, single-stranded DNAs, each of about 1 kb and encoding only one protein. Here, the use of cloned full-length FBNYV DNAs for reproducing FBNYV-like symptoms in Vicia faba, the principal natural host of FBNYV, is reported. Characteristic symptoms of FBNYV infection were obtained in faba bean plants following biolistic DNA delivery or agroinoculation with all eight FBNYV DNAs. Although the eight different DNAs have been invariably detected in field samples infected with the various geographical FBNYV isolates, experimental infection with different combinations of fewer than eight DNAs also led to typical FBNYV symptoms. Even only five genome components, DNA-R, DNA-S, DNA-M, DNA-U1 and DNA-U2, were sufficient for inducing disease symptoms in V. faba upon agroinoculation. Symptomatic plants agroinoculated or bombarded with eight DNAs contained typical FBNYV virions; however, the virus was not transmitted by Aphis craccivora or Acyrthosiphon pisum, two efficient aphid vectors of FBNYV.